The naked truth - Van De Beek, A (Nederduitse Gereformeerde Teologiese Tydskrif, 2007)
The author argues that truth is the result of experiences that provide us with data that display a structure and provide people with a comprehensive symbolic universe wherein everything was originally included – even science and religion. After the religious wars in seventeenth century Europe turned to a more limited concept of truth, scientific evidence became dominant. In spite of attempts to introduce history and, later, human relations into scholarly work, this idea remained dominant for many people. The author argues that, in practice, human beings do not maintain these generalisations because truth based on unique experiences is decisive. The most unique is a person – in the case of Christian faith, the person of Jesus. That cannot be argued. He is the truth that presents itself as the naked truth of the hanged man on the cross.